Immigration and the Future of the Welfare State in Europe. Issue 1 (September 2021) - Alesina, Alberto; Harnoss, Johann; Rapoport, Hillel
We analyze the effect of immigration on attitudes toward income redistribution in twenty-eight European countries over the period 2002 to 2012, before the "refugee crisis." We find that native workers lower their support for redistribution if the share of immigration in their country is high. This effect is larger for individuals who hold negative views regarding immigration but is smaller when immigrants are culturally closer to natives and come from richer-origin countries. The effect also varies with native workers' and immigrants' education: more educated natives support more redistribution if immigrants are also relatively educated. Overall, our results show that the negative effect of immigration on attitudes toward redistribution is relatively small and is counterbalanced among skilled natives by positive second-order effects for the quality and diversity of immigration.